Angelica polysaccharide-loaded biological scaffold and application thereof in repairing full-thickness cartilage defect
The biological scaffold loaded with angelica polysaccharides was prepared by 3D printing technology, and the combination of poly(lactic acid-glycolic acid) nano microspheres and PCL/PDA scaffolds was solved, and the problem of repair of full-thickness cartilage defects was achieved, efficient drug release and chondrocyte proliferation effects were achieved, providing an effective repair solution for full-thickness cartilage defects.
Patent Information
- Application Number
- CN202411889298.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to effectively repair full-thickness cartilage defects, especially when the defect area is large, and the type and quality of the repaired cartilage cannot be ensured.
Biostents loaded with angelica polysaccharides were prepared by 3D printing technology, and the angelica polysaccharides were wrapped with poly(lactic acid-glycolic acid) nano microspheres were used to wrap the angelica polysaccharides and combined with PCL/PDA scaffolds to form a biological scaffold with targeting and controlled release characteristics, accurately matching the anatomical structure of the repair site.
The efficient fitting and drug release of biological scaffolds loaded with angelica polysaccharides in the repair of full-thickness cartilage defects has been achieved, which has improved the drug loading rate and encapsulation rate, enhanced the proliferation and repair effect of chondrocytes, and provided an effective basic framework for full-thickness cartilage defects.
Smart Images

Figure BDA0005200227470000091 
Figure BDA0005200227470000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biological scaffolds, in particular to a biological scaffold loaded with angelica polysaccharide and application thereof in repairing full-thickness cartilage defects. Background Art
[0002] Entering the 21st century, China has moved from a sports power to a sports powerhouse, and sports are becoming increasingly popular. At the same time, full-thickness cartilage defects caused by sports injuries are becoming more and more common. Full-thickness cartilage defects are usually difficult to treat conservatively because they often form "scar healing." At present, surgical treatment is the main treatment, and there are different options depending on the size of the defect: bone marrow stimulation technology (debridement + microfracture), which is based on the principle of using mesenchymal stem cells in the bone marrow to differentiate into chondrocytes to repair the wound, but it is only suitable for defects less than 1 cm 2 and the type of cartilage that is repaired cannot be determined.
[0003] Angelica polysaccharide has important applications in the field of full-thickness cartilage defect repair. Angelica polysaccharide can promote chondrocyte proliferation, increase the number of chondrocytes, facilitate the filling of defect sites, and promote stem cells to differentiate into chondrocytes. In the repair process, it induces stem cells to transform into chondrocytes and participate in cartilage defect repair. In addition, Angelica polysaccharide has the effects of activating complement activity, scavenging free radicals, and enhancing immunity, and also has a significant effect on the hematopoietic system.
[0004] Poly(lactic-glycolic acid) nanoparticle carriers have unique targeting properties, which can improve drug stability and reduce toxic side effects. As a new type of drug delivery carrier in recent years, drug-loaded nanoparticles use safe, non-toxic, and biodegradable polymer materials as encapsulation carriers to deliver drugs to target organs. They can not only enhance drug selectivity and efficacy and reduce toxic side effects, but also pass through the interstitial space of tissue cells to achieve controlled release of drugs and prolong the duration of action. In addition, while ensuring the drug's effect, the dosage can be reduced, drug degradation can be slowed down, drug stability can be improved, and drug toxic side effects can be further reduced or avoided. Summary of the invention
[0005] 1. Technical problems solved:
[0006] In view of the shortcomings of the prior art, the present invention provides a biological scaffold loaded with angelica polysaccharide and its application in repairing full-thickness cartilage defects. By using 3D printing technology, the biological scaffold loaded with angelica polysaccharide can be processed into a shape that accurately matches the anatomical structure of the part to be repaired, so that it can better fit the defect, provide a suitable basic framework for cartilage repair, and bring hope to the development of full-thickness cartilage defect repair materials and technological innovation.
[0007] (II) Technical solution:
[0008] (1) Add water to a reaction vessel, then add lactic acid and glycolic acid, stir and mix, dehydrate at 150-160° C. and normal pressure for 2-3 hours, then reduce the pressure to 12-14 kPa and react for 2-3 hours, and react at 1-1.5 kPa for 4-5 hours to generate a lactic acid-glycolic acid prepolymer.
[0009] (2) Add a lactic acid-glycolic acid prepolymer with a mass ratio of 100:(0.3-0.5) and a catalyst into a reaction vessel, increase the vacuum degree of the pressurizing device to 100-120 Pa, react for 16-24 hours, add chloroform, filter, extract, and dry to obtain poly(lactic acid-glycolic acid).
[0010] (3) crushing the angelica powder, washing it with an ethanol-water solution, heat-treating it at 70-80° C., filtering it with suction, and vacuum drying it to obtain angelica powder. Then, extracting the angelica powder with hot water, centrifuging it in a centrifuge for 20-30 minutes, combining the supernatants, adjusting the pH to 4.5-5, centrifuging it in a centrifuge for 20-30 minutes, concentrating the supernatants, adding an ethanol-water solution, letting it stand, filtering it, washing it with anhydrous ethanol, acetone, and ether in sequence, and drying it to obtain an angelica polysaccharide extract.
[0011] (4) The angelica polysaccharide extract is dissolved in water to prepare a 2-3 mg / mL polysaccharide solution, and poly(lactic acid-glycolic acid) is dissolved in dichloromethane to prepare a 25-30 mg / mL poly(lactic acid-glycolic acid) solution. The polysaccharide solution and the poly(lactic acid-glycolic acid) solution are mixed, and ultrasonic emulsification is performed for 60-70 seconds, and the mixture is added dropwise to a 1-1.5% polyvinyl alcohol solution. The ultrasonic emulsification is continued for 30-40 seconds, and the mixture is stirred for 3-5 hours. The mixture is centrifuged in a centrifuge at 10,000-12,000 r / min for 10-20 minutes, and the precipitate is removed, washed, and freeze-dried to obtain poly(lactic acid-glycolic acid)-coated angelica polysaccharide nanospheres.
[0012] (5) After the poly (lactic acid-glycolic acid)-coated Angelica polysaccharide nanospheres are dispersed into a suspension with distilled water, the suspension is magnetically stirred at 150-200 r / min for 2-4 hours, and then the PCL / PDA scaffold is added and freeze-dried to obtain a biological scaffold loaded with Angelica polysaccharide.
[0013] Preferably, in step (2), the catalyst is a mixture of toluenesulfonic acid and stannous chloride in a molar ratio of 1:(0.9-1.2).
[0014] Preferably, in step (4), the volume ratio of the polysaccharide solution to the poly(lactic acid-glycolic acid) solution is 1:(7.5-8.5).
[0015] Preferably, the preparation method of the PCL / PDA scaffold is: adding a polycaprolactone scaffold to a tris hydrochloride buffer, then adding dopamine hydrochloride, stirring in the dark for 18-24 hours, then taking out the scaffold, washing it with deionized water for 3-5 times, and then freeze-drying it to obtain a PCL / PDA scaffold.
[0016] Preferably, the ratio of the tris hydrochloride buffer to dopamine hydrochloride is 1L:(1.5-4)g.
[0017] Preferably, the pH of the tris hydrochloride buffer is 8.5.
[0018] Preferably, the present invention can accurately process biomaterials into tissue engineering scaffolds that match the anatomical structure shape and have controllable internal pore size and shape.
[0019] (III) Beneficial technical effects: The present invention constructs a porous polycaprolactone scaffold through 3D printing technology and chemically modifies it with polydopamine to increase the hydrophilicity of the scaffold; at the same time, poly (lactic acid-glycolic acid) nanoparticles are prepared to encapsulate angelica polysaccharide and combine with the PCL / PDA scaffold to form an angelica polysaccharide biological scaffold for repairing full-thickness cartilage defects.
[0020] As shown in Table 1-Table 2, the drug loading rate, encapsulation rate and drug release within one month of the embodiment of the present invention are higher than those of the control example. Because Angelica polysaccharide can promote the proliferation of chondrocytes and promote the repair of cartilage defects, and poly (lactic acid-glycolic acid) nanoparticles are easily phagocytosed by cells and have strong targeting, which helps to maintain the stability of Angelica polysaccharide. The combination of the two generates poly (lactic acid-glycolic acid)-coated Angelica polysaccharide nanoparticles, which can increase the drug release, drug loading rate and encapsulation rate; PDA is a substance with strong adhesion, which can be used to modify the surface of various materials including super-hydrophobic surfaces. PDA-modified PCL can make poly (lactic acid-glycolic acid)-coated Angelica polysaccharide nano-microspheres adhere to the PCL / PDA scaffold to form an Angelica polysaccharide bioscaffold, which increases the hydrophilicity of the scaffold and creates a good microenvironment for chondrocytes and other cells to grow and function on the scaffold. With the help of 3D printing technology, the Angelica polysaccharide bioscaffold can be processed into a shape that accurately matches the anatomical structure of the part to be repaired, so that it can better fit the defect, provide a basic framework for cartilage repair, and bring hope to the development of full-thickness cartilage defect repair materials and technological innovation. DETAILED DESCRIPTION
[0021] Embodiment 1:
[0022] (1) A polycaprolactone scaffold was added to 1 L of tris hydrochloride buffer solution with a pH of 8.5, and then 4 g of dopamine hydrochloride was added. After stirring in the dark for 24 hours, the scaffold was taken out, washed with deionized water for 5 times, and freeze-dried to obtain a PCL / PDA scaffold.
[0023] (2) Water is added to a reaction vessel, and then 3 mol of lactic acid and 3.6 mol of glycolic acid are added and mixed. The mixture is dehydrated at 160° C. and normal pressure for 2 h. The mixture is then depressurized to 13.3 kPa and reacted for 2 h. The mixture is then reacted at 1.3 kPa for 5 h to generate a lactic acid-glycolic acid prepolymer.
[0024] (3) 100 g of lactic acid-glycolic acid prepolymer and 0.5 g of a catalyst are added to a reaction container, wherein the catalyst is a mixture of toluenesulfonic acid and stannous chloride in a molar ratio of 1:1.2. The vacuum degree of the pressurizing device is increased to 120 Pa. After reacting for 16 hours, chloroform is added, filtered, extracted, and dried to obtain poly(lactic acid-glycolic acid).
[0025] (4) The angelica powder is crushed, washed with 100 mL of 80% ethanol aqueous solution, heat-treated at 80° C., filtered, and vacuum-dried to obtain angelica powder. The angelica powder is then extracted with hot water, centrifuged in a centrifuge for 30 min, the supernatant is combined, the pH is adjusted to 4.5, and centrifuged again for 20 min. The supernatant is concentrated, 400 mL of 95% ethanol aqueous solution is added, the mixture is allowed to stand, filtered, washed with anhydrous ethanol, acetone, and ether in sequence, and dried to obtain an angelica polysaccharide extract.
[0026] (5) The angelica polysaccharide extract was dissolved in water to prepare a 3 mg / mL polysaccharide solution, and poly(lactic acid-glycolic acid) was dissolved in dichloromethane to prepare a 25 mg / mL poly(lactic acid-glycolic acid) solution. 30 mL of the polysaccharide solution was mixed with 255 mL of the poly(lactic acid-glycolic acid) solution, and ultrasonically emulsified for 60 s, and then added dropwise to a 1% polyvinyl alcohol solution. The ultrasonic emulsification was continued for 30 s, and the mixture was stirred for 3 h. The mixture was centrifuged at 12,000 r / min for 20 min, and the precipitate was removed, washed, and freeze-dried to obtain poly(lactic acid-glycolic acid)-coated angelica polysaccharide nanospheres.
[0027] (6) The poly (lactic acid-glycolic acid)-coated Angelica polysaccharide nanospheres were dispersed into a suspension with distilled water, and then magnetically stirred at 200 r / min for 2 hours, and then added to the PCL / PDA scaffold and freeze-dried to obtain a biological scaffold loaded with Angelica polysaccharide.
[0028] Embodiment 2:
[0029] (1) A polycaprolactone scaffold was added to 1 L of tris hydrochloride buffer solution with a pH of 8.5, and then 3 g of dopamine hydrochloride was added. After stirring in the dark for 20 hours, the scaffold was taken out, washed with deionized water for 4 times, and freeze-dried to obtain a PCL / PDA scaffold.
[0030] (2) Add water to a reaction vessel, then add 3 mol of lactic acid and 3 mol of glycolic acid, stir and mix, dehydrate at 160° C. and normal pressure for 2 h, then reduce the pressure to 13.3 kPa and react for 2 h, and then react at 1.3 kPa for 5 h to generate a lactic acid-glycolic acid prepolymer.
[0031] (3) 100 g of lactic acid-glycolic acid prepolymer and 0.3 g of a catalyst are added to a reaction container, wherein the catalyst is a mixture of toluenesulfonic acid and stannous chloride in a molar ratio of 1:0.9. The vacuum degree of the pressurizing device is increased to 100 Pa. After reacting for 24 hours, chloroform is added, filtered, extracted, and dried to obtain poly (lactic acid-glycolic acid).
[0032] (4) The angelica powder is crushed, washed with 100 mL of 80% ethanol aqueous solution, heat-treated at 70° C., filtered, and vacuum-dried to obtain angelica powder. The angelica powder is then extracted with hot water, centrifuged in a centrifuge for 20 min, the supernatant is combined, the pH is adjusted to 5, and centrifuged again in a centrifuge for 30 min. The supernatant is concentrated, 400 mL of 95% ethanol aqueous solution is added, the mixture is allowed to stand, filtered, washed with anhydrous ethanol, acetone, and ether in sequence, and dried to obtain an angelica polysaccharide extract.
[0033] (5) The angelica polysaccharide extract was dissolved in water to prepare a 2 mg / mL polysaccharide solution, and poly(lactic acid-glycolic acid) was dissolved in dichloromethane to prepare a 30 mg / mL poly(lactic acid-glycolic acid) solution. 30 mL of the polysaccharide solution was mixed with 225 mL of the poly(lactic acid-glycolic acid) solution, and ultrasonically emulsified for 70 seconds, and then added dropwise to a 1.5% polyvinyl alcohol solution. The ultrasonic emulsification was continued for 40 seconds, and the mixture was stirred for 5 hours. The mixture was centrifuged at 10,000 r / min for 10 minutes, and the precipitate was removed, washed, and freeze-dried to obtain poly(lactic acid-glycolic acid)-coated angelica polysaccharide nanospheres.
[0034] (6) The poly (lactic acid-glycolic acid)-coated Angelica polysaccharide nanospheres were dispersed into a suspension with distilled water, and then magnetically stirred at 150 r / min for 4 hours, and then added to the PCL / PDA scaffold and freeze-dried to obtain a biological scaffold loaded with Angelica polysaccharide.
[0035] Embodiment 3:
[0036] (1) The polycaprolactone scaffold was added to 1 L of tris hydrochloride buffer solution with a pH of 8.5, and then 1.5 g of dopamine hydrochloride was added. After stirring in the dark for 24 hours, the scaffold was taken out, washed with deionized water for 5 times, and freeze-dried to obtain a PCL / PDA scaffold.
[0037] (2) Add water to a reaction vessel, then add 3 mol of lactic acid and 3 mol of glycolic acid, stir and mix, dehydrate at 150° C. and normal pressure for 2 h, then reduce the pressure to 13.3 kPa and react for 2 h, and then react at 1.3 kPa for 4 h to generate a lactic acid-glycolic acid prepolymer.
[0038] (3) 100 g of lactic acid-glycolic acid prepolymer and 0.5 g of a catalyst are added to a reaction container, wherein the catalyst is a mixture of toluenesulfonic acid and stannous chloride in a molar ratio of 1:1. The vacuum degree of the pressurizing device is increased to 120 Pa. After reacting for 20 hours, chloroform is added, filtered, extracted, and dried to obtain poly(lactic acid-glycolic acid).
[0039] (4) The angelica powder is crushed, washed with 100 mL of 80% ethanol aqueous solution, heat-treated at 70° C., filtered, and vacuum-dried to obtain angelica powder. The angelica powder is then extracted with hot water, centrifuged in a centrifuge for 30 minutes, the supernatants are combined, the pH is adjusted to 5, and centrifuged again for 20 minutes. The supernatants are concentrated, 400 mL of 95% ethanol aqueous solution is added, the mixture is allowed to stand, filtered, washed with anhydrous ethanol, acetone, and ether in sequence, and dried to obtain an angelica polysaccharide extract.
[0040] (5) The angelica polysaccharide extract was dissolved in water to prepare a 2 mg / mL polysaccharide solution, and poly(lactic acid-glycolic acid) was dissolved in dichloromethane to prepare a 30 mg / mL poly(lactic acid-glycolic acid) solution. 30 mL of the polysaccharide solution was mixed with 225 mL of the poly(lactic acid-glycolic acid) solution, and ultrasonically emulsified for 60 s, and then added dropwise to a 1% polyvinyl alcohol solution. The ultrasonic emulsification was continued for 40 s, and stirred for 5 h. The mixture was centrifuged at 12,000 r / min for 20 min, and the precipitate was removed, washed, and freeze-dried to obtain poly(lactic acid-glycolic acid)-coated angelica polysaccharide nanospheres.
[0041] (6) The poly (lactic acid-glycolic acid)-coated Angelica polysaccharide nanospheres were dispersed into a suspension with distilled water, and then magnetically stirred at 200 r / min for 4 hours, and then added to the PCL / PDA scaffold and freeze-dried to obtain a biological scaffold loaded with Angelica polysaccharide.
[0042] Embodiment 4:
[0043] (1) The polycaprolactone scaffold was added to 1 L of tris hydrochloride buffer solution with a pH of 8.5, and then 4 g of dopamine hydrochloride was added. After stirring for 18 hours in the dark, the scaffold was taken out, washed with deionized water three times, and freeze-dried to obtain a PCL / PDA scaffold.
[0044] (2) Add water to a reaction vessel, then add 3 mol of lactic acid and 3.6 mol of glycolic acid, stir and mix, dehydrate at 160° C. and normal pressure for 2 h, then reduce the pressure to 13.3 kPa and react for 2 h, and then react at 1.3 kPa for 5 h to generate a lactic acid-glycolic acid prepolymer.
[0045] (3) 100 g of lactic acid-glycolic acid prepolymer and 0.5 g of a catalyst are added to a reaction container, wherein the catalyst is a mixture of toluenesulfonic acid and stannous chloride in a molar ratio of 1:1.2. The vacuum degree of the pressurizing device is increased to 120 Pa. After reacting for 24 hours, chloroform is added, filtered, extracted, and dried to obtain poly(lactic acid-glycolic acid).
[0046] (4) The angelica powder is crushed, washed with 100 mL of 80% ethanol aqueous solution, heat-treated at 70° C., filtered, and vacuum-dried to obtain angelica powder. The angelica powder is then extracted with hot water, centrifuged in a centrifuge for 20 min, the supernatant is combined, the pH is adjusted to 4.5, and centrifuged in a centrifuge for 30 min. The supernatant is concentrated, 400 mL of 95% ethanol aqueous solution is added, the mixture is allowed to stand, filtered, washed with anhydrous ethanol, acetone, and ether in sequence, and dried to obtain an angelica polysaccharide extract.
[0047] (5) The angelica polysaccharide extract was dissolved in water to prepare a 3 mg / mL polysaccharide solution, and poly(lactic acid-glycolic acid) was dissolved in dichloromethane to prepare a 25 mg / mL poly(lactic acid-glycolic acid) solution. 30 mL of the polysaccharide solution was mixed with 255 mL of the poly(lactic acid-glycolic acid) solution, and ultrasonically emulsified for 70 seconds, and then added dropwise to a 1% polyvinyl alcohol solution. The ultrasonic emulsification was continued for 40 seconds, and the mixture was stirred for 5 hours. The mixture was centrifuged at 10,000 r / min for 10 minutes, and the precipitate was removed, washed, and freeze-dried to obtain poly(lactic acid-glycolic acid)-coated angelica polysaccharide nanospheres.
[0048] (6) The poly (lactic acid-glycolic acid)-coated Angelica polysaccharide nanospheres were dispersed into a suspension with distilled water, and then magnetically stirred at 150 r / min for 2 hours, and then added to the PCL / PDA scaffold and freeze-dried to obtain a biological scaffold loaded with Angelica polysaccharide.
[0049] Comparative Example 1:
[0050] (1) Water is added to a reaction vessel, and then 3 mol of lactic acid and 3.6 mol of glycolic acid are added and mixed. The mixture is dehydrated at 160° C. and normal pressure for 2 h. The mixture is then depressurized to 13.3 kPa and reacted for 2 h. The mixture is then reacted at 1.3 kPa for 5 h to generate a lactic acid-glycolic acid prepolymer.
[0051] (2) 100 g of lactic acid-glycolic acid prepolymer and 0.5 g of a catalyst are added to a reaction container, wherein the catalyst is a mixture of toluenesulfonic acid and stannous chloride in a molar ratio of 1:1.2. The vacuum degree of the pressurizing device is increased to 120 Pa. After reacting for 16 hours, chloroform is added, filtered, extracted, and dried to obtain poly(lactic acid-glycolic acid).
[0052] (3) The angelica powder is crushed, washed with 100 mL of 80% ethanol aqueous solution, heat-treated at 80° C., filtered, and vacuum-dried to obtain angelica powder. The angelica powder is then extracted with hot water, centrifuged in a centrifuge for 30 min, the supernatant is combined, the pH is adjusted to 4.5, and centrifuged again for 20 min. The supernatant is concentrated, 400 mL of 95% ethanol aqueous solution is added, the mixture is allowed to stand, filtered, washed with anhydrous ethanol, acetone, and ether in sequence, and dried to obtain an angelica polysaccharide extract.
[0053] (4) The angelica polysaccharide extract was dissolved in water to prepare a 3 mg / mL polysaccharide solution, and poly(lactic acid-glycolic acid) was dissolved in dichloromethane to prepare a 25 mg / mL poly(lactic acid-glycolic acid) solution. 30 mL of the polysaccharide solution was mixed with 255 mL of the poly(lactic acid-glycolic acid) solution, and ultrasonically emulsified for 60 s, and then added dropwise to a 1% polyvinyl alcohol solution. The ultrasonic emulsification was continued for 30 s, and the mixture was stirred for 3 h. The mixture was centrifuged at 12,000 r / min for 20 min, and the precipitate was removed, washed, and freeze-dried to obtain poly(lactic acid-glycolic acid)-coated angelica polysaccharide nanospheres.
[0054] (5) The poly (lactic acid-glycolic acid)-coated Angelica polysaccharide nanospheres were dispersed into a suspension with distilled water, and then magnetically stirred at 200 r / min for 2 hours, and then the PCL scaffold was added and freeze-dried to obtain a biological scaffold loaded with Angelica polysaccharide.
[0055] 5 mg of each biological scaffold sample loaded with Angelica polysaccharide of the embodiment and the comparative example was weighed, added to 20 mL of dichloromethane, completely dissolved under magnetic stirring, and extracted by adding 10 mL of PBS buffer solution, fully mixed on a vortex mixer for 20 min, and allowed to stand for 1 h to separate the aqueous phase from the oil phase and collect the aqueous phase. The remaining oil phase was treated again by repeating the above method, the aqueous phase solutions collected from the two separations were mixed, centrifuged at 3000 r / min for 10 min, the supernatant was taken, and the absorbance at 480 nm was measured by an ultraviolet spectrophotometer. The content of Angelica polysaccharide extract in the separated solution was calculated according to the standard curve. The experiment was repeated 3 times, and the average value was taken to calculate the drug loading and encapsulation rate of Angelica polysaccharide extract in the scaffold, respectively. Drug loading = drug mass contained in the scaffold / total mass of the scaffold × 100%, and encapsulation rate = drug mass contained in the scaffold / total mass of the drug input × 100%.
[0056] 15 mg of each sample of the embodiment and the comparative example was weighed, uniformly dispersed in 10 mL of PBS buffer solution, loaded into a sealed dialysis bag, placed in 75 mL of buffer solution, and dialyzed at a constant speed (100 r / min) in an air shaker at 37° C. to simulate the in vivo physiological environment. 10 mL of the dialysate was taken out at intervals of 4 h, 12 h, 24 h, 36 h, 48 h, 60 h, 72 h, 96 h, and 120 h, respectively, and 10 mL of fresh PBS was added to maintain the total volume unchanged. The absorbance of the dialysate was determined by ultraviolet spectrophotometry. The experiment was repeated 3 times, the average value was taken, and the drug release within one month was calculated according to the standard curve.
[0057] Table 1 shows the drug loading rate and encapsulation efficiency of the samples
[0058] Drug loading (%) Encapsulation rate (%) Example 1 10.21 94.34 Example 2 9.89 96.52 Example 3 10.13 94.65 Example 4 10.02 95.31 Comparative Example 1 2.82 87.56
[0059] Table 1 shows the drug release of the samples within one month
[0060]
[0061]
[0062] As shown in Tables 1 and 2, the drug loading rate, encapsulation rate and drug release within one month of the embodiment are higher than those of the control example. Because Angelica polysaccharide can promote the proliferation of chondrocytes and promote the repair of cartilage defects, and poly (lactic acid-glycolic acid) nanoparticles are easily phagocytosed by cells and have strong targeting, which helps to maintain the stability of Angelica polysaccharide. The combination of the two generates poly (lactic acid-glycolic acid)-coated Angelica polysaccharide nanoparticles, which can increase drug release, drug loading rate and encapsulation rate; PDA is a substance with strong adhesion, which can be used to modify the surface of various materials including super-hydrophobic surfaces. PDA-modified PCL can make poly (lactic acid-glycolic acid)-coated Angelica polysaccharide nano-microspheres adhere to the PCL / PDA scaffold to form an Angelica polysaccharide bioscaffold, which increases the hydrophilicity of the scaffold and creates a good microenvironment for chondrocytes and other cells to grow and function on the scaffold. With the help of 3D printing technology, the Angelica polysaccharide bioscaffold can be processed into a shape that accurately matches the anatomical structure of the part to be repaired, so that it can better fit the defect, provide a basic framework for cartilage repair, and bring hope to the development of full-thickness cartilage defect repair materials and technological innovation.
Claims
1. A method for preparing a biological scaffold loaded with Angelica polysaccharide, characterized in that: The preparation method comprises: (1) adding water to a reaction vessel, then adding lactic acid and glycolic acid, stirring and mixing, dehydrating at 150-160° C. and normal pressure for 2-3 hours, then reducing the pressure to 12-14 kPa for reaction for 2-3 hours, and reacting at 1-1.5 kPa for 4-5 hours to generate a lactic acid-glycolic acid prepolymer; (2) adding the lactic acid-glycolic acid prepolymer and the catalyst into a reaction vessel, increasing the vacuum degree of the pressurizing device to 100-120 Pa, reacting for 16-24 hours, adding chloroform, filtering, extracting, and drying to obtain poly(lactic acid-glycolic acid); (3) crushing the angelica powder, washing it with an ethanol aqueous solution, heat-treating it at 70-80° C., filtering it with suction, and vacuum drying it to obtain angelica powder, then extracting the angelica powder with hot water, centrifuging it in a centrifuge for 20-30 minutes, combining the supernatants, adjusting the pH to 4.5-5, centrifuging it in a centrifuge for 20-30 minutes, concentrating the supernatants, adding an ethanol aqueous solution, letting it stand, filtering it, washing it with anhydrous ethanol, acetone, and ether in sequence, and drying it to obtain an angelica polysaccharide extract; (4) dissolving the angelica polysaccharide extract in water to prepare a 2-3 mg / mL polysaccharide solution, dissolving poly(lactic acid-glycolic acid) in dichloromethane to prepare a 25-30 mg / mL poly(lactic acid-glycolic acid) solution, mixing the polysaccharide solution and the poly(lactic acid-glycolic acid) solution, performing ultrasonic intermittent emulsification for 60-70 seconds, and dropping the mixture into a 1-1.5% polyvinyl alcohol solution, continuing ultrasonic emulsification for 30-40 seconds, stirring for 3-5 hours, and centrifuging in a centrifuge at 10000-12000 r / min for 10-20 minutes. Taking out the precipitate, washing it, and freeze-drying it to obtain poly(lactic acid-glycolic acid)-coated angelica polysaccharide nanoparticles; (5) After the poly (lactic acid-glycolic acid)-coated Angelica polysaccharide nanospheres are dispersed into a suspension with distilled water, the suspension is magnetically stirred at 150-200 r / min for 2-4 hours, and then the PCL / PDA scaffold is added and freeze-dried to obtain a biological scaffold loaded with Angelica polysaccharide.
2. The method for preparing the angelica polysaccharide-loaded bioscaffold according to claim 1, characterized in that: In the step (1), the molar ratio of lactic acid to glycolic acid is 1:(1-1.2).
3. The method for preparing the biological scaffold loaded with Angelica polysaccharide according to claim 1, characterized in that: In the step (2), the mass ratio of the lactic acid-glycolic acid prepolymer to the catalyst is 100:(0.3-0.5).
4. The method for preparing the angelica polysaccharide-loaded bioscaffold according to claim 1, characterized in that: In the step (2), the catalyst is a mixture of toluenesulfonic acid and stannous chloride in a molar ratio of 1:(0.9-1.2).
5. The method for preparing the angelica polysaccharide-loaded bioscaffold according to claim 1, characterized in that: In the step (4), the volume ratio of the polysaccharide solution to the poly(lactic acid-glycolic acid) solution is 1:(7.5-8.5).
6. The method for preparing the biological scaffold loaded with Angelica polysaccharide according to claim 1, characterized in that: The preparation method of the PCL / PDA scaffold is as follows: a polycaprolactone scaffold is added to a tris hydrochloride buffer solution, and then dopamine hydrochloride is added. After stirring in the dark for 18-24 hours, the scaffold is taken out, washed with deionized water for 3-5 times, and then freeze-dried to obtain a PCL / PDA scaffold.
7. The method for preparing the biological scaffold loaded with Angelica polysaccharide according to claim 2, characterized in that: The ratio of the tris hydrochloride buffer to dopamine hydrochloride is 1L:(1.5-4)g.
8. The method for preparing the biological scaffold loaded with Angelica polysaccharide according to claim 7, characterized in that: The pH of the tris hydrochloride buffer is 8.
5.
9. Use of the Angelica polysaccharide bioscaffold according to claims 1-8 in repairing full-thickness cartilage defects, characterized in that: It is able to precisely process biomaterials into tissue engineering scaffolds that match the anatomical structure, with controllable internal pore size and shape.